Autonomous Solutions in Servitization : A Comprehensive Research Analysis - Mia, Md Abdullah (My University, 2025)
In this research, a systematic literature review of the autonomous solution in servitization has been conducted. As the world is shifting towards more artificial intelligence, the need for self-driven optimised service is becoming more demanding day by day. Servitization happens when manufacturing companies change from only selling products to also offering services. Instead of just making and selling things, they add services to improve their offerings. To provide better service, continuous monitoring of the product is essential. Instead of monitoring the service manually, it is required to monitor continuously for enabling the digital business service efficiently. The continuous monitoring service will give real time data of the product which will help the company to provide more value to customers and create new business opportunities. The integration of autonomous solutions and servitization requires an intensive analysis of current progress of the digital business and technology research for a better understanding of the technology and business models. For this purpose, research articles have been accumulated from different sources and the analysis has been performed using data text mining approach. Data text mining was used because it plays an important role in extracting valuable insights from service interactions, improving decision-making, and optimizing service performance. We tried to filter relevant studies, identify trends, and gain insights for servitization and autonomous solutions using semi-automated tools and algorithms using dynamic topic modeling. This research explores the role of autonomous technologies in servitization, their impact on business performance, and the research gap associated with implementation. Additionally, technology readiness level measurement has been used in this research to know about the research stage of each cluster. Technology readiness level helps to evaluate the maturity and readiness for deployment in servitization models. The findings highlight the strategic importance of autonomous solutions in reshaping the manufacturing industry.
Keywords: cluster analysis; data mining; machine learning; artificial intelligence; services; service business; clusters; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; Master's Programme in Sustainable and Autonomus Systems (SAS); Sustainable and Autonomous Systems